Comparative Efficacy of Two Different Synchronization Protocol in Postpartum Dairy Cows - Hirole, P.D.; Deshmukh, S. G.; Ingawale, M.V.; Kuralkar, S. V.; Thorat, M. G.; Ratnaparkhi, A. R.; Godbole, P.V. (International Journal of Livestock Research, 2018)
The study was undertaken to find out the efficacy of Ovsynch and Double PGF2α protocol in terms of estrus induction, time required for onset of induced estrus, duration of induced estrus and conception rate in postpartum dairy cows. Total twelve cows with 40-60 postpartum days from 2nd to 4th lactation were selected and divided into two groups comprising six cows in each group. In Group-I cows received Ovsynch protocol with 18 to 20 hrs. fixed TAI. In Group-II cows were treated with Double PGF2α protocol and inseminated after detected estrus. The first service conception rate was recorded on day 60 post insemination. The percent induced estrus response recorded in Ovsynch group was 83.33 and Double PGF2α group 100 percent, respectively. The time required for onset of induced estrus and duration of induced estrus observed in Ovsynch and Double PGF2α protocol was 53.20±1.8; 21.2±0.58 and 50.67±1.54; 21.33±0.49, respectively. The first service conception rate was 33.33 percent observed in Ovsynch and double PGF2α group, respectively. The percent induced estrus response was numerically higher in PGF2 group as compared to Ovsynch group whereas the first service conception rate in Ovsynch and double PGF2α group was at par.